Classification using FTIR and UV-Vis spectra combined with chemometrics and GC-MS profiles of Brucea javanica fruit extracts with different extracting solvents - Triawan, Deni Agus; Banon, Charles; Nurwidiyani, Ria; Adfa, Morina (Jurnal Riset Kimia, 2025)
Brucea javanica L. Merr. has long been used for its antimalarial, anti-diabetic, antibacterial, and antioxidant effects. Its bioactivity depends on both its chemical constituents and the type of solvent employed during extraction. Integrating FTIR and UV-Vis spectral data with chemometric approaches enables classification of fruit extracts based on the solvent used, while GC-MS analysis provides detailed compound identification. Using sonication, extraction with methanol, ethyl acetate, and n-hexane produced yields of 30.61% ± 0.80, 19.20% ± 0.75, and 18.12% ± 0.89, respectively. FTIR spectra were recorded over 600–4000 cm⁻¹, and UV-Vis spectra were measured across 200–800 nm. Analysis showed that ethyl acetate and n-hexane extracts exhibited similar profiles, which differed from that of the methanol extract. PCA successfully distinguished all three extracts, with cumulative PC1 and PC2 values above 70%. FTIR-based PCA provided better separation due to its broader fingerprint region compared to UV-Vis spectra. GC-MS results revealed that the compound profiles were largely similar across the extracts, although more compounds were detected in the methanol extract than in the ethyl acetate or n-hexane extracts.